Inflation threshold effects on stock prices: Evidence from the plantation sector in Malaysia - Vui, Ken Wong; Saizal Pinjaman (Macrothink Institute, 2025)
This study aims to examine the threshold effect of inflation on stock prices in the Malaysian plantation sector. This study used earnings per share (EPS) and return on equity (ROE) as proxies for microeconomic variables, and inflation (INF which proxies for the consumer price index) as a proxy for macroeconomic variables. A panel dataset covering 32 listed companies in the plantation sector from 2008Q3 to 2023Q3 is used. The results of threshold analysis show that inflation has a nonlinear effect, with a threshold value of 4.6128%. This implies that when inflation crosses this value, it significantly alters the outcome of stock prices. Inflation consistently has a negative effect on stock prices across both regimes, although the impact slightly decreases under higher inflation. Higher inflation will increase the detrimental effects of ROE and reverses the significance effect of EPS and DTE to insignificant, while enhancing the positive contributions of revenue and operating cash flow.